Tanggung Jawab Majelis Pengawas Daerah Terhadap Penyerahan Penyimpanan Protokol Notaris yang Berumur Lebih Dari 25 Tahun - Nandita Mentari Nasution; Lutfina Mustafi Nadia HAM (Jurnal Ilmu Kenotariatan, 2024)
The issue at hand is the storage of Notary Protocol documents that are 25 years or older, which are still held by the receiving notary. The transfer of Notary Protocol documents aged 25 years or older from the receiving notary to the Regional Supervisory Board has not been carried out to date. The reason for this non-execution of the transfer is the lack of available storage space for these Notary Protocol documents. The research methodology employed in this study is a normative juridical approach, utilizing both statutory and conceptual approaches. Data collection is conducted through literature review, with materials categorized accordingly. Once all legal materials have been gathered, they are analyzed descriptively and qualitatively, focusing on reasoning. The implementation of regulations set forth in the Notary Law cannot be carried out as instructed due to the Regional Supervisory Board's lack of a designated storage space for Notary Protocols. The accountability of the Regional Supervisory Board regarding protocol storage is crucial and significant, given the direct authority delegated by the Notary Law to the Regional Supervisory Board in storing Notary Protocols aged 25 years or older. The legal vacuum regarding sanctions applicable to the Regional Supervisory Board is a contributing factor to the Board's negligence in its responsibilities.. KEYWORDS: Regional Supervisory Council, Notary Protocol, UUJN.